Ameliorative Effects of Infantile Feire Kechuan Oral Solution on Mycoplasma Pneumoniae Pneumonia in Infant Mouse and Rat Models. (17th September 2018) - Guo, Shanshan; Bao, Lei; Qu, Tiange; Mao, Xin; Gao, Yingjie; Xu, Yingli; Cui, Xiaolan
Abstract : Mycoplasma pneumoniae (MP) infection is a major pathogen of community-acquired pneumonia (CAP) in children worldwide. Infantile Feire Kechuan Oral Solution (IFKOS) has been used for the treatment of MP pneumonia clinically in China for many years. The present study was designed to investigate the therapeutic effect of IFKOS on MP pneumonia and explore the potential mechanism of the actions. The infant BALB/c mouse and Wistar rat models of MP infection were successfully established to confirm the therapeutic effects of IFKOS, followed by assays for related cytokines and investigations of the IgM response involved. The results showed that IFKOS exhibited an inhibitory effect on pulmonary index (PI) and effectively reduced the degree of lesions in the lungs. The lethal rate of mice was significantly decreased while survival time of mice was dramatically increased by IFKOS treatment in comparison to infection control, respectively. IFKOS treatment (40, 20, and 10ml/kg) significantly decreased the level of MP-IgM in a dose-dependent manner, whereas IFKOS showed no obvious inhibitory effect on the increase of relative expression of MP-DNA. In addition, the elevated IL-2 and TNF- α levels were significantly reduced and the decreased IL-6 level was significantly enhanced by IFKOS treatment. Our study demonstrates that IFKOS has inhibitory effect on MP infection in infant mouse and rat models of MP pneumonia and protective effect from lethal MP challenge in infant murine model. These anti-MP effects might be related to suppression of the IgM response and a reversal the imbalance of Th1/Th2 cytokines induced by MP infection.